Spin-offs from space technology to cultural life - Jong-bum Kim (International Journal of Advanced Culture Technology(IJACT), 2017)
In this paper, we examine the points of similarity and difference between Korea, Japan, and the USA in terms of the spin-off effects of space technology on cultural life. In Japan and the USA, spin-off effects of space development research by government funded research centers are diffusive while in Korea they are interruptive. Spin-offs of research results impact cultural life via technology transfer and commercialization in businesses. This is because the Korean aerospace industry has progressed largely based on an overall system, but the promotion of internal parts and sub-systems, which can trigger technological development and spin-off effects in manufacturing, has been neglected. In the case of the KARI, the government funded research center, we argue that it is necessary for KARI to devote more resources to transfer (or promote spin-offs of) space technology to small and medium-sized businesses and other industries.